2016
DOI: 10.1080/10826084.2016.1197261
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists' Perspectives on Dispensing Medications With the Potential for Misuse, Diversion, and Intentional Overdose: Results of a Province-Wide Survey of Community Pharmacists in Canada

Abstract: Findings from this study demonstrated a need for improved systems for managing patients at risk for medication misuse, diversion, and overdose. Strategies that warrant further attention for limiting the means of medication misuse include increased access to electronic medical records and providing additional continuing education support for community pharmacists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 11 publications
1
28
1
Order By: Relevance
“…Attitudes and practice strategies of pharmacists towards drug misuse management and the relevance of years of practice experience were discussed in seven studies . The majority of pharmacists recruited by Leong et al and Patel et al had greater than 10 years pharmacy practice experience, and 50% of the respondents interviewed by Fendrich et al had greater than 20 years practice experience. Butler and Sheridan reported that community pharmacists with greater practice experience were more willing to confront patients about drug misuse.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Attitudes and practice strategies of pharmacists towards drug misuse management and the relevance of years of practice experience were discussed in seven studies . The majority of pharmacists recruited by Leong et al and Patel et al had greater than 10 years pharmacy practice experience, and 50% of the respondents interviewed by Fendrich et al had greater than 20 years practice experience. Butler and Sheridan reported that community pharmacists with greater practice experience were more willing to confront patients about drug misuse.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen articles reported that pharmacists felt they had gaps in knowledge related to addiction and pain management, or in the misuse potential of over‐the‐counter and opioid medications . Pharmacists in a qualitative study by Hagemeier et al, that specifically explored pharmacists' perceptions of the behaviours of patients who were misusing drugs and the associated challenges reported that they felt they lacked the knowledge to deal with aggressive and intimidating patient behaviour .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To thwart drug diversion, physicians are helped by the development of new tools before prescribing, such as ‘prescription drug monitoring programs’, even if some practitioners disagree with the idea of using it (usability, dissatisfaction, erosion of physician autonomy) [7]. Community pharmacists also use educational supports and data-sharing projects for the management of patients suspected to be at high risk for drug diversion [8, 9]. In hospitals, pharmacists are responsible for the safe use of medications by reducing the risk of adverse events through medication reconciliation.…”
Section: Discussionmentioning
confidence: 99%